phân tích \(x^6+27\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1-27x^3\)
\(=1-\left(3x\right)^3\)
\(=\left(1-3x\right)\left(1+3x+9x^2\right)\)
\(---\)
\(x-3^3+27\)
\(=x-27+27=x\)
\(---\)
\(27x^3+27x^2+9x+1\)
\(=\left(3x\right)^3+3\cdot\left(3x\right)^2\cdot1+3\cdot3x\cdot1^2+1^3\)
\(=\left(3x+1\right)^3\)
\(---\)
\(\dfrac{x^6}{27}-\dfrac{x^4y}{3}+x^2y^2-y^3\) (sửa đề)
\(=\left(\dfrac{x^2}{3}\right)^3-3\cdot\left(\dfrac{x^2}{3}\right)^2\cdot y+3\cdot\dfrac{x^2}{3}\cdot y^2-y^3\)
\(=\left(\dfrac{x^2}{3}-y\right)^3\)
#Ayumu
ta có: x6 +27=(x2)3 +33
=(x2+3)(x4 - 3x2 +9)
phân tích thành nhân tử: x^3/27+x^6/729+10x^3/9
= x^3/27+x^6/729+10x^3/9
= 10x^12/177147
nha bạn
`a, 8x^3 - 1 = (2x-1)(4x^2 + 2x - 1)`
`b, x^3 + 27y^3 = (x+3y)(x^3 - 3xy + 9y^2)`
`c, x^3 - y^6 = (x-y^2)(x+xy^2 + y^4)`
\(x^2-5x+6\)
\(=x^2-2x-3x+6\)
\(=x\left(x-2\right)-3\left(x-2\right)\)
\(=\left(x-3\right)\left(x-2\right)\)
\(27x^3-\frac{1}{27}\)
\(=\left(3x\right)^3-\left(\frac{1}{3}\right)^3\)
\(=\left(3x-\frac{1}{3}\right)\left(9x^2+x+\frac{1}{9}\right)\)
<=>x9-9x6-27
<=>(x3)3-3(x3)23+3.9.x3-27-27x3
<=>(x3-3)3-27x3
<=>(x3-3-3x).((x3-3)2+(x3-3).3x+9x2)
<=>(x3-3-3x).(x6-6x3+9+3x4-9x+9x2)
Bài 1:
a) \(x^3-16x=x\left(x-4\right)\left(x+4\right)\)
b) \(3x^2+3y^2-6xy-12=3\left(x^2-2xy+y^2-4\right)=3\left(x-y-2\right)\left(x-y+2\right)\)
c) \(x^2+6x+5=\left(x+1\right)\left(x+5\right)\)
d) \(x^4+x^3+2x^2+x+1=\left(x^2+x+1\right)\left(x^2+1\right)\)
Bài 2:
a) Ta có: \(\left(x+6\right)^2=144\)
\(\Leftrightarrow\left[{}\begin{matrix}x+6=12\\x+6=-12\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-18\end{matrix}\right.\)
b) Ta có: \(x^3+27+\left(x+3\right)\left(x-9\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x^2-3x+9\right)+\left(x+3\right)\left(x-9\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x^2-3x+9+x-9\right)=0\)
\(\Leftrightarrow x\left(x+3\right)\left(x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-3\\x=2\end{matrix}\right.\)
c) Ta có: \(2x^2-x-6=0\)
\(\Leftrightarrow2x^2-4x+3x-6=0\)
\(\Leftrightarrow2x\left(x-2\right)+3\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(2x+3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-\dfrac{3}{2}\end{matrix}\right.\)
\(x^6+27=\left(x^2\right)^3+3^3=\left(x^2+3\right)\left(x^4-3x^2+9\right)\)
\(=\left(x^2+3\right)\left(x^4+6x^2-9x^2+9\right)\)
\(=\left(x^2+3\right)\left(x^4+6x^2+9-9x^2\right)\)
\(=\left(x^2+3\right)\left[\left(x^2+3\right)^2-9x^2\right]\)
\(=\left(x^2+3\right)\left[\left(x^2+3\right)^2-\left(3x\right)^2\right]\)
\(=\left(x^2+3\right)\left(x^2+3-3x\right)\left(x^2+3+3x\right)\)
=(x2)3+33 = (x2+3)(x4-3x2+9)